Audit of waist measurement methods during statutory diving medical assessments. (6th November 2021) - Williams, N; Moore, A; Woods, M; Forman, S
Abstract: Background: Measurement of waist circumference is used to assess abdominal fat and risk of heart disease, type 2 diabetes, cancer and stroke. It is performed in several clinical settings for health promotion and medical assessment purposes, including statutory medical assessments where results may influence decisions on fitness to work. Under the Diving at Work Regulations 1997, working divers must have an annual assessment of their fitness to dive performed by an approved medical examiner of divers (AMED), appointed by the Health and Safety Executive (HSE). The assessment includes measurement of height, weight and waist circumference, the latter used as an indicator of central adiposity and associated health risks. Aims: To establish the practice of AMEDs in measuring waist circumference of working divers undergoing medical assessment to determine their fitness to dive. Methods: Ninety-seven AMEDs were sent a questionnaire and asked to describe their current practice in measuring waist circumference. The response rate was 79%. The audit standard used was the consensus document published by the World Health Organization (WHO). Results: Of the 77 responses, 76 were completed sufficiently to allow analysis. When the waist was measured, there was consistency in the diver's level of clothing, stage of breathing and posture for the procedure but variability in the site of measurement. Only 7/76 (9%) respondents carried out waist measurement fully in line with WHO guidance. Conclusions: The audit has identified that there is a need for guidance for AMEDs on measuring waist circumference in the statutory medical assessment of working divers.